The Effectiveness of Disaster Risk Communication: A Systematic Review of Intervention Studies - Bradley, Declan T (Public Library of Science, 2014)
Introduction: A disaster is a serious disruption to the functioning of a community that exceeds its capacity to cope within its own resources. Risk communication in disasters aims to prevent and mitigate harm from disasters, prepare the population before a disaster, disseminate information during disasters and aid subsequent recovery. The aim of this systematic review is to identify, appraise and synthesise the findings of studies of the effects of risk communication interventions during four stages of the disaster cycle. Methods: We searched the Cochrane Central Register of Controlled Trials, Embase, MEDLINE, PsycInfo, Sociological Abstracts, Web of Science and grey literature sources for randomised trials, cluster randomised trials, controlled and uncontrolled before and after studies, interrupted time series studies and qualitative studies of any method of disaster risk communication to at-risk populations. Outcome criteria were disaster-related knowledge and behaviour, and health outcomes. Results: Searches yielded 5,224 unique articles, of which 100 were judged to be potentially relevant. Twenty-five studies met the inclusion criteria, and two additional studies were identified from other searching. The studies evaluated interventions in all four stages of the disaster cycle, included a variety of man-made, natural and infectious disease disasters, and were conducted in many disparate settings. Only one randomised trial and one cluster randomised trial were identified, with less robust designs used in the other studies. Several studies reported improvements in disaster-related knowledge and behaviour. Discussion: We identified and appraised intervention studies of disaster risk communication and present an overview of the contemporary literature. Most studies used non-randomised designs that make interpretation challenging. We do not make specific recommendations for practice but highlight the need for high-quality randomised trials and appropriately-analysed cluster randomised trials in the field of disaster risk communication where these can be conducted within an appropriate research ethics framework.